PROTAGONIS PEREMPUAN EMPAT NOVEL ARYANTI DALAM PEMBACAAN SUBALTERN POSKOLONIALISME - Made Jiwa Atmaja (Journal Social and Humaniora, 2017)
This paper presents a research report female protagonist in the four novels Aryanti, namely Selembut Bunga , Hidup Perlu Akar, Dunia Tak Berhenti Berputar and Getaran-getaran . The fourth novel narrates the search for identity fourth female protagonist in an e?ort to explore the potential of feminism to be placed on equal footing not only the competencies that are gender, but also mondial. Mondialisasi process is mirrored by a series of events that describe the relationships between nations, across cultures and transnation. Behind the events that seem simple and everyday, in fact contained the views of the author are so serious in response to cultural globalization process is in progress and dealing with local culture (Java), and national levels. In cross-cultural, identity clearly a problem that should be redefined. Keywords: femenisme, post-colonial and subaltern third world